Process Optimization and Wear Performance of Plasma-Cladding Fe5 Coatings on Rotary Tillage Blades - Jiang Zeng; Yinggang Ma; Zhichao Fang; Mingliang Wu; Zhili Wu; Mingkai Lei (Applied Sciences)
Objective: This study was conducted to address the harsh working environment of agricultural machinery and improve the wear resistance of soil-contacting components such as rotary tiller blades, thereby extending their service life. Method: Plasma-cladding technology was employed to prepare an iron-based wear-resistant coating on the surface of rotary tiller blades. The following parameter combination was optimized using response surface methodology (RSM): a cladding current of 144A, a cladding speed of 23 mm/s, a powder feeding rate of 23 g/min, and a cladding distance of 12 mm. The microstructure morphology, phase composition, microhardness, and wear resistance of the wear-resistant cladding layer were investigated. Results: The results indicate that the interface of the cladding layer is clean and free from significant porosity or defects, exhibiting good metallurgical bonding with the substrate. The primary phases identified in the cladding layer include α-Fe, Cr7C3, Cr2Fe14C, and Cr-Ni-Fe-C solid solutions. The average hardness of the cladding layer is 1171 Hv0.5, approximately 2.9 times that of the substrate. In wet sand–rubber wheel wear tests under identical conditions, the weight loss of the cladding layer is only 1/21 that of 65Mn steel, with minimal wear morphology. Field trials showed that the wear of the cladding layer rotary tiller blade was reduced by 24.5% compared with the unclad blade. The presence of the cladding layer significantly protected the integrity of the cutting edge, ensuring the functionality of the rotary tiller blade in cutting and throwing soil; thus, its original appearance was maintained even after prolonged wear. The findings of this study can provide a valuable reference for the enhancement of wear resistance for other soil-contacting components.